Development of a Diabetes Mellitus Knowledge Resource for Clinical Decision Support Assisting Primary Care Physicians With Work-Related Issues. Issue 11 (November 2017) - Allen, Anna; Welch, Laura; Kirkland, Katherine; Trout, Douglas; Baron, Sherry
Abstract : Objective: The aim of this study was to describe the process by which a group of subject matter experts (SMEs) in the area of occupational health and primary care developed a clinical decision support (CDS) tool addressing work-related issues, which are important in the care of patients with diabetes mellitus (DM). The CDS is intended for primary care clinicians caring for employed adults with DM. Methods: The SME's selected guidelines for the management of DM in working adults, reviewed pertinent literature, and developed specific recommendations for action in the clinical setting. Results: Multiple factors at work may adversely affect DM management. Clinicians can support working patients through education and care strategies to improve control. Conclusion: Improved recognition of factors at work that can have an impact on DM care provides opportunities for improved management of DM among working adults.